1990
DOI: 10.1093/oxfordjournals.jbchem.a123066
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Major Sialidases of Various Types of Rat Blood Cells: Their Comparison with Rat Liver Sialidases1

Abstract: The substrate specificity and subcellular location of the major sialidases of three types of rat blood cells were characterized and compared with those of the known three types of rat liver sialidase, which have been designated intralysosomal, cytosolic, and plasma membrane-associated sialidases. Platelets and leucocytes contain mainly an acid sialidase, which is highly active towards oligosaccharides and 4MU-NeuAc, and erythrocytes possess a high level of a sialidase acting on gangliosides. A Percoll gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
2

Year Published

1994
1994
2006
2006

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
1
13
2
Order By: Relevance
“…Sialidases have been described in the lysosomal matrix as a single protein or associated with ␤-galactosidase and the carboxypeptidase protective protein/cathepsin A (PPCA) to form a large molecular mass complex (Verheijen et al, 1985) and as a polypeptide strictly associated with lysosomal membrane Miyagi and Tsuiki, 1984;Sagawa et al, 1990;Zeigler et al, 1989). In human a lysosomal sialidase is implicated in two lysosomal storage disorders: sialidosis, which is due to a structural alteration in the sialidase gene (Thomas and Beaudet, 1995), and galactosialidosis, in which the absence of PPCA is responsible for the combined lack of the two lysosomal hydrolases (d 'Azzo et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Sialidases have been described in the lysosomal matrix as a single protein or associated with ␤-galactosidase and the carboxypeptidase protective protein/cathepsin A (PPCA) to form a large molecular mass complex (Verheijen et al, 1985) and as a polypeptide strictly associated with lysosomal membrane Miyagi and Tsuiki, 1984;Sagawa et al, 1990;Zeigler et al, 1989). In human a lysosomal sialidase is implicated in two lysosomal storage disorders: sialidosis, which is due to a structural alteration in the sialidase gene (Thomas and Beaudet, 1995), and galactosialidosis, in which the absence of PPCA is responsible for the combined lack of the two lysosomal hydrolases (d 'Azzo et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Should the ability of erythrocyte sialidase to affect GDla and GM1 be linked to the chemical difference between the enzymes solubilized by detergent and phospholipase C, further study of the structure/function relationship of the sialidase activity towards gangliosides would be required. In addition, rat erythrocyte membrane sialidase showed little or no hydrolyzing activity towards MeUmb-NeuAc, sialyllactose, fetuin and orosomucoid [13]. However, rabbit erythrocyte membrane sialidase exhibited high activity towards MeUmb-NeuAc, sialyllactose and glycopeptides but no activity towards the glycoproteins tested.…”
Section: Discussionmentioning
confidence: 89%
“…It has been reported that no sialidase activity toward MeUmb-NeuAc or mixed gangliosides was found in cytosolic fractions of erythrocytes, platelets and leucocytes from rat blood cells [13]. Human leucocyte sialidase activity was also not detected in the cytosolic fraction [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations